1999
DOI: 10.1515/ijsl.1999.140.77
|View full text |Cite
|
Sign up to set email alerts
|

Language maintenance and shift among Vietnamese in America

Abstract: Thepurpose ofthis study was to determine the amount oflanguage shift and language maintenance of Vietnamese in a large urban center in California.To determine language use in the Community, 106 Vietnamese parents were surveyed. A definite language shift could be seen within the families. There were a substantial number of homes where both English and Vietnamese were spoken. Approximately one-fifth of the children spoke only English among themselves while one-third spoke both languages. Income and parents' educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…A large body of research has shown that pressures for language shift are significant in many language minority families and communities (e.g., DeKlerk, 2000;McCarty, Romero-Little, & Zepeda, 2006;Sandel, Chao, & Liang, 2006;Shin, 2005;Vail, 2006;Young & Tran, 1999). Observations of different communities that come into contact with a majority language have shown that there is almost always a complete shift in language use within three generations barring any special effort (Fishman, 1991).…”
Section: Heritage-language Learning and Maintenancementioning
confidence: 99%
“…A large body of research has shown that pressures for language shift are significant in many language minority families and communities (e.g., DeKlerk, 2000;McCarty, Romero-Little, & Zepeda, 2006;Sandel, Chao, & Liang, 2006;Shin, 2005;Vail, 2006;Young & Tran, 1999). Observations of different communities that come into contact with a majority language have shown that there is almost always a complete shift in language use within three generations barring any special effort (Fishman, 1991).…”
Section: Heritage-language Learning and Maintenancementioning
confidence: 99%
“…Based on these results, Young and Tran (1999) reported a rapid rate of shift from Vietnamese to English in this population. Language shift was defined as a decrease in the number of speakers of a language or a decrease in L1 use across domains.…”
Section: Linguistic Issues Across Generationsmentioning
confidence: 73%
“…According to the 2000 U. S. Census (Reeves & Bennett, 2004), there are an estimated 1.12 million Vietnamese in the United States, making this group the fourth largest Asian American population following Chinese, Filipinos, and Asian Indians. Within the past 30 years, there have been various studies on Vietnamese socialization, adaptation to the United States, and language maintenance and shift (Bankston & Zhou, 1995;Chung, 2000;Luong, 1990;McDonald, 2000;Nguyen, Shin & Krashen, 2001;Pham, 1990;Young & Tran, 1999;Zhou & Bankston, 1994.…”
Section: Social Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of its students, roughly 1250, are from families with low socio-economic status and face financial difficulties; approximately 1200 are local HK students and around 50 are immigrant mainland Chinese. Previous studies conducted in Western contexts indicate that immigrants' length of stay in the host country and age of immigration influence their heritage language maintenance and identity formation (Luo and Wiseman 2000;Young and Tran 1999). The younger children immigrate and the longer they stay in the host country, the less likely they are to maintain their ethnic language and to identify with their ethnic identity.…”
Section: The Studymentioning
confidence: 99%